Hemorrhage from the Major Duodenal Papilla after Endoscopic Retrograde Cholecystopancreatography - M. P. Mantserov; Ye. V. Moroz; V. L. Astashov (Общая реаниматология)
Hemorrhage from the major duodenal papilla (MDP) is a most common complication of endoscopic retrograde cholecystopancreatography (ERCPG) with/without papillosphincterotomy (PST).The objective of the present study was to estimate the frequency of this complication and to evaluate the efficiency of methods for its prevention.Subjects and methods: In 1994 to 2005, the N. N. Burdenko Main Military Hospital performed 1373 ERCPGs with/without PST. The patients were divided into 2 groups: 1) 326 patients (males, 75.1%; mean age, 58.2±16.1 years) who had no drug preventive therapy for postmanipulation complications and PST was performed by the routine procedure; 2) 1047 patients (males, 71.9%; mean age, 56.3±14.5 years) who had endoscopic (PST being performed, by using atypical or combined procedures) and drug (octreotide and protease inhibitors) prevention of complications. The incidence of hemorrhage from MDP and a need for endoscopic bleeding arrest were estimated.Results: Just after the manipulation, hemorrhage requiring endoscopic arrest occurred in 24 (7.3%) and 43 (4.1%) patients in Groups 1 and 2, respectively (p<0.001). Following 24 hours, hemorrhage developed in 6 (13.9%) and 3 (3.9%) patients (p<0.001), this requiring surgical intervention in 1 (2.3%) and 2 (26%) patients from Groups 1 and 2, respectively. After 48 hours, hemorrhage recurred in 1 patient in each of the study groups and the signs of unstable hemostasis in esogaso-duodenoscopy (Forrest 2 a,b) were detected in 6 (139%) and 5 (6.6%) patients in Groups 1 and 2, respectively (p<0.05).Conclusion: After ERCPG with PST, hemorrhage occurs in 4.9% of the patients. PST by atypical and combined procedures and the administration of octreotide and protease inhibitors effectively reduce the risk of this complication.